Contesting authentic Islam: Ahlul Quran movements and performance of debates in the religious sphere of Kerala. (1st December 2019) - Shafeeque, K. P. Abdul
AbstractAhlul Quran movements introduced the debates on the question of the authority of tradition as the second source of Islamic knowledge and critiqued the existing notions of Islam among the Malabar Muslims in Kerala. These intra-Islamic factions attempted to reinterpret Islam according to their interpretations solely based on the Quran and developed their take on what constitutes 'authentic Islam'. This article uses Ahlul Quran as a generic term for the two main Ahlul Quran movements that developed in the Malabar Coast during the early and late half of the twentieth century. These two movements were the Ahlul Quran movement of Pazhayangadi by B. Kunjahamed Haji and Khuran Sunnath Society of Abul Hasan (popularly known as Chekanur Moulavi). They initiated numerous oral debates and discussions with various Islamic groups existing in the Malabar region such as Sunnis, Mujahids, Ahmediyyas and Jamaat-e-Islami, challenging and contesting different notions of 'authentic Islam'. Along with oral debates, it also gave birth to textual contestations, with voluminous books, articles and pamphlets challenging each other. This article traces the intra-religious debates that developed among the Malabar Muslims after the emergence of Ahlul Quran thoughts. It analyses how the existing Islamic groups upholding different versions of 'authentic Islam' in the Malabar region, located in the northern part of Kerala, South India, challenged the growth of these Ahlul Quran movements. In short, during the numerous debates and contestations that happened between the Islamic groups within the Malabar region the article explores how these debates are a constant performance of Islam and its tradition.